Evaluation of Nurse’s Competency Concerning Delivered Care and Pedagogy in Nursing at Emergency Unite: Comparative Study - Ali Refak Lazem,; Huda Baker Hassan, (AlQalam Journal of Medical and Applied Sciences, 2024)
Many countries have an accumulated need for health care in hospitals and increasing patients' desire to get the best possible care with the rise of job requirements and the increasing complexity of nursing services such as client-centered and holistic patient care, nurses' professional competency is gaining increasing attention. The importance of ensuring nurses' competency has been emphasized at a global level. an Observational design study was conducted from 25 December 2023 to 25 March 2024. The study setting was conducted at the emergency department in AI-Hussein Teaching Hospital, Al-Shatra General Hospital in Thi-Qar governorate/Iraq.A purposive sample (non-probability) involving (103 nurses:60 in Al-Hussien Hospital and 43 in Al-Shatra. The practices were evaluated by using the observational checklist. The data was analyzed by using (SPSS version 23). the result in both hospitals, the majority of participants were in age groups (20-25) years old, graduated from the Nursing Institute graduates, the experience in nursing was (1-5 years) and their experience in the emergency unit was (1-5 years) and of them had 1-5 courses. in Al-Shatra Hospital A high of them work at evening shift at 58.1%, and in AL-Hussein Hospital which is 81.7 %. A high percentage of them work at morning shift the study concluded that the nurses’ competency concerning delivered care and pedagogy in nursing at emergency units for patients was moderate level in the two hospitals They recommended enrolling nurses in training courses and continuing follow-up for nursing competency. في ظل تزايد الحاجة إلى الرعاية الصحية في المستشفيات في العديد من البلدان ورغبة المرضى المتزايدة في الحصول على أفضل رعاية ممكنة مع ارتفاع متطلبات الوظائف والتعقيد المتزايد لخدمات التمريض مثل رعاية المرضى الشاملة والمتمركزة حول العميل، تكتسب الكفاءة المهنية للممرضات اهتمامًا متزايدًا. وقد تم التأكيد على أهمية ضمان كفاءة الممرضات على المستوى العالمي. أجريت دراسة تصميمية مراقبة من 25 ديسمبر 2023 إلى 25 مارس 2024. أجريت الدراسة في قسم الطوارئ في مستشفى الحسين التعليمي، مستشفى الشطرة العام في محافظة ذي قار / العراق. عينة قصدية (غير احتمالية) شملت (103 ممرضة: 60 في مستشفى الحسين و 43 في الشطرة. تم تقييم الممارسات باستخدام قائمة المراجعة المراقبة. تم تحليل البيانات باستخدام (SPSS الإصدار 23). النتيجة في كلا المستشفيين، كانت غالبية المشاركين في الفئات العمرية (20-25) سنة، خريجي معهد التمريض، كانت الخبرة في التمريض (1-5 سنوات) وخبرتهم في وحدة الطوارئ (1-5 سنوات) وكان لديهم 1-5 دورات. في مستشفى الشطرة يعمل معظمهم في فترة المساء بنسبة 58.1٪، وفي مستشفى الحسين 81.7٪ %. يعمل نسبة عالية منهم في الفترة الصباحية وخلصت الدراسة إلى أن كفاءة الممرضات فيما يتعلق بالرعاية المقدمة وأسلوب التدريس في التمريض في أقسام الطوارئ للمرضى كانت بمستوى متوسط في المستشفيين وأوصت بتسجيل الممرضات في دورات تدريبية ومتابعة مستمرة لكفاءة التمريض